ON THE LITTLE KNOWN SPECIES OF THREADFIN BREAMS NEMIPTERUS MESOPRION (BLEEKER)AND NEMIPTERUS DELAGOAE (SMITH) - JOHN, SOPHY; HAMEED, M SHAHUL (Fishery Technology, 2017)
Among the fish species of the family Nemipteridae, the two little known species, namely, Nemipterus mesoprion (Bleeker) and Nemipterus delagoae (Smith) are recorded from the Cochin waters. Nemipterus mesoprion is a new di&tributional record from the west coast of India. N. delagoae is described with adequate number& of specimem for the first time from Indian waters. Moreover, the results of the present study show that the colour of the viscera, the number of pyloric caeca and the gill rakers can also be used for the diagnosis of the species of the genus Nemipterus. The affinity of the above species with other related specie of the genus Nemipterus and their geographical distribution are presented